King-Devick test in wheelchair sports: Identifying normative values and effects of exertion on outcomes - Barfield, J.-P.; Linens, S.; Mickle, A. (Clinical Journal of Sport Medicine, 2023)
Objective: To establish normative baseline values on the King-Devick (KD) Test for contact wheelchair sport participants. The secondary purpose was to examine the effect of physical exertion on test score.